Personal capabilities and social factor towards entrepreneurial intention: empirical evidence of Science and Technology undergraduate students / Jati Kasuma ... [et al.] - Kasuma, Jati; Sapenee, Mohd Kassim; Sheikh Naimullah, Bibi Sarpinah; Adenan, Mohd Amirul; Abang Abdul Rahman, Dayang Hummida (Universiti Teknologi Mara, Selangor: Puncak Alam Campus, 2019)
Entrepreneurial intention is one of the focus and attention among researchers nowadays. The younger generation is encouraged to get involved in entrepreneurship. It may able to overcome the issue of unemployment rate by creating more job opportunities. The purpose of this study is to examine the relationship and influence of Personal Capabilities and Social Factors towards entrepreneurial intention among Science & Technology students. A total of 214 respondents of science and technology undergraduate students from both Universiti Malaysia Sarawak (UNIMAS) and Universiti Teknologi MARA (UiTM) Sarawak participated in the survey. The empirical results indicate that social factors were found to have positive relationship and significantly correlated with entrepreneurial intention. On the other hand, the relationship between personal capabilities and entrepreneurial intention was found to have a significant albeit weak positive relationship with entrepreneurial intention. Implication and future research direction are also discussed.